Functionalized Semiconducting Carbon Nanotubes: Three Models for Carrier Spectra - Lykah, V.A.; Syrkin, E.S. (Хімія, фізика та технологія поверхні, 2010)
Electronic spectra in functionalizing semiconducting carbon nanotube (CNT) are researched theoretically. The soft degrees of freedom are considered in the molecular system: radial deformation, misfit dislocations, and conformation. For each model the selfconsistent system of equations is derived. A system describes a charge carrier longitudinal quantization in CNT, interaction of a carrier in CNT and molecular electric dipoles, material equations for a soft degree of freedom and its reconstruction. It is shown that the functionalization reconstructs the CNT electronic spectra and creates different conditions of localization or tunneling for holes and electrons.